Pengaruh Gaya Kepemimpinan, Disiplin dan Motivasi Kerja Terhadap Kinerja Pegawai Milenial di PT PLN (PERSERO) UP3 PALEMBANG - Reysia Chelsy Santoso; Juhaini Alie (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of leadership style, work discipline, and work motivation on the performance of millennial employees at PT PLN (Persero) UP3 Palembang. The research is motivated by the predominance of the millennial generation in the workplace, which has unique characteristics and high expectations for a flexible, supportive, and participatory work environment. A quantitative approach was used, employing descriptive methods and multiple linear regression analysis. The sample consisted of 123 millennial employees selected through a saturated sampling technique. The results show that leadership style, work discipline, and motivation simultaneously have a significant effect on employee performance, with an F-value of 76.702 and a significance level of 0.000. Partially, all three variables also have a significant effect with t-values of: leadership style (46.59), work discipline (21.60), and work motivation (34.08). The coefficient of determination (R2) is 0.951, indicating that 95.1% of the variation in millennial employee performance is explained by these three variables. Work motivation is the most dominant factor influencing performance. This study provides managerial implications in improving motivation systems, implementing participative leadership styles, and enforcing discipline through educational approaches to optimize millennial employee performance at PT PLN (Persero) UP3 Palembang.